Hyperamylasemia and acute pancreatitis after pancreatoduodenectomy: two different entities - Loos, Martin; Strobel, Oliver; Dietrich, Maximilian; Mehrabi, Arianeb; Ramouz, Ali; Saeedi, Mohammed al; Müller, Beat P.; Diener, Markus K.; Schneider, Martin; Berchtold, Christoph; Feißt, Manuel; Hinz, Ulf; et al. (Surgery, 2021)
Background - Serum amylase activity greater than the institutional upper limit of normal (hyperamylasemia) on postoperative day 0-2 has been suggested as a criterion to define postoperative acute pancreatitis after pancreatoduodenectomy, but robust evidence supporting this definition is lacking. - Background - To assess the clinical impact of hyperamylasemia after pancreatoduodenectomy and to define postoperative acute pancreatitis. - Methods - Data of 1,235 consecutive patients who had undergone pancreatoduodenectomy between January 2010 and December 2014 were extracted from a prospective database and analyzed. Postoperative acute pancreatitis was defined based on the computed tomography severity index. Logistic regression modeling was used to calculate the postoperative acute pancreatitis rate of the entire study population. - Results - Hyperamylasemia on postoperative day 1 was found in 52% of patients after pancreatoduodenectomy. Patients with hyperamylasemia on postoperative day 1 had statistically significantly greater morbidity and mortality than patients with a normal serum amylase activity on postoperative day 1 with the rates of postoperative pancreatic fistula of 14.5% vs 2.1%, and 90-day mortality of 6.6% vs 2.2%, respectively. Of the 364 patients who underwent postoperative computed tomography, 103 (28%) had radiologic signs of acute pancreatitis, thus defining them as having postoperative acute pancreatitis by our definition. Logistic regression modeling showed a 14.7% rate of postoperative acute pancreatitis for the entire patient cohort and 29.2% for patients with hyperamylasemia on postoperative day 1. Outcomes of patients with postoperative acute pancreatitis defined based on the computed tomography severity index showed a rate of postoperative pancreatic fistula of 32.4% and a 90-day mortality rate of 11.8%, which were worse than those of patients with hyperamylasemia on postoperative day 1 alone. - Conclusion - Hyperamylasemia on postoperative day 1 is a frequent finding after pancreatoduodenectomy, but hyperamylasemia on postoperative day 1 alone is not synonymous with postoperative acute pancreatitis because only 29.2% of such patients have acute pancreatitis based on computed tomography findings. Postoperative acute pancreatitis is a dangerous complication after pancreatoduodenectomy, but its prevalence, according to the gold standard of CT, is not as high as reported previously. Our data suggest that hyperamylasemia on postoperative day 1 and postoperative acute pancreatitis are 2 different entities.